2019
DOI: 10.1038/s42003-019-0611-3
|View full text |Cite
|
Sign up to set email alerts
|

An improved neuroanatomical model of the default-mode network reconciles previous neuroimaging and neuropathological findings

Abstract: The brain is constituted of multiple networks of functionally correlated brain areas, out of which the default-mode network (DMN) is the largest. Most existing research into the DMN has taken a corticocentric approach. Despite its resemblance with the unitary model of the limbic system, the contribution of subcortical structures to the DMN may be underappreciated. Here, we propose a more comprehensive neuroanatomical model of the DMN including subcortical structures such as the basal forebrain, cholinergic nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
242
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 291 publications
(271 citation statements)
references
References 169 publications
(185 reference statements)
28
242
0
1
Order By: Relevance
“…Our evaluations furthermore suggested that predictive performance increased when including both baseline and trajectory data, and when complementing cortical manifold features with subcortical connectivity estimates. These findings reemphasize benefits of incorporating subcortical nodes in the characterization of large-scale cortical network organization and overall cognitive function 108,109 .…”
Section: Iqmentioning
confidence: 78%
“…Our evaluations furthermore suggested that predictive performance increased when including both baseline and trajectory data, and when complementing cortical manifold features with subcortical connectivity estimates. These findings reemphasize benefits of incorporating subcortical nodes in the characterization of large-scale cortical network organization and overall cognitive function 108,109 .…”
Section: Iqmentioning
confidence: 78%
“…While sensory-motor cortices are primary cortices (i.e. idiotypic areas Mesulam, 1998) and the default-mode network has been associated with transmodal higher-order functions (Margulies et al, 2016, Alves et al 2019. The principal gradient may thus represent one fundamental principle driving a hierarchical organisation of cognitive functions (Huntenburg, Bazin, & Margulies, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothalamus is not included in the functional connectivity gradient, although it also belongs to the olfactocentric system. As one limitation of surface analyses is that they notoriously underestimate deep subcortical structures, this may might explain this discrepancy (Alves et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The other system arises from the hippocampus and progressively radiates medially along the cingulate cortex to reach the dorsolateral frontal cortex and superior parietal lobule, this system is referred to as hippocampocentric (for a comprehensive review on the dual origin see Pandya et al, 2017). Introducing functional gradients into this framework, the principal gradient seems to be represented by the hippocampocentric system (for anatomical reviews see Alves et al, 2019;Catani et al, 2013). This system is crucial for limbic and transmodal cognitive functions (e.g.…”
mentioning
confidence: 99%